2012
DOI: 10.2147/ceg.s36569
|View full text |Cite
|
Sign up to set email alerts
|

A plausible explanation for male dominance in typhoid ileal perforation

Abstract: The phenomenon of consistent male dominance in typhoid ileal perforation (TIP) is not well understood. It cannot be explained on the basis of microbial virulence, Peyer’s patch anatomy, ileal wall thickness, gastric acidity, host genetic factors, or sex-linked bias in hospital attendance. The cytokine response to an intestinal infection in males is predominantly proinflammatory as compared with that in females, presumably due to differences in the sex hormonal milieu. Sex hormone receptors have been detected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
(55 reference statements)
1
13
1
Order By: Relevance
“…However, Khan M et al proposed that genetic and host inflammatory response also play a role. 8 High grade fever followed by abdominal pain was the most consistent feature as also seen in various studies. 5 Three patients presented with psychosis.…”
Section: Discussionsupporting
confidence: 70%
“…However, Khan M et al proposed that genetic and host inflammatory response also play a role. 8 High grade fever followed by abdominal pain was the most consistent feature as also seen in various studies. 5 Three patients presented with psychosis.…”
Section: Discussionsupporting
confidence: 70%
“…Other studies also reported a similar gender distribution [1,13,16,17]. Plausible explanation for this male predominance is the fact that males have more outdoor exposure and are more likely to consume street foods as compared to females in Pakistani society [1,13,17]. Street food consumption is an important risk factor for enteric fever [18].…”
Section: Discussionmentioning
confidence: 74%
“…Certain gastrointestinal infections are more recurrent and severe in men than in women. This sexual dimorphism can be explained in part because of behavioral differences during hygiene and eating practices, such as handwashing before food handling and eating, storage, refrigeration, and defrosting practices, and tendency of men to eat undercooked or raw food, as well as to ingest roadside food [ 30 ]. Although sexual dimorphism in gastrointestinal infections is mainly due to immune differences, these differences in turn can be influenced by the above mentioned behavioral dissimilarities between women and men.…”
Section: Sexual Dimorphism and Bacterial Infections In The Gastrointementioning
confidence: 99%
“…Although sexual dimorphism in gastrointestinal infections is mainly due to immune differences, these differences in turn can be influenced by the above mentioned behavioral dissimilarities between women and men. This is the case of typhoid fever and its complication: typhoid ileal perforation (TIP) [ 30 ]. TIP is characterized by an exacerbated inflammatory activity at Peyer’s patches, probably in response to Salmonella typhi exposure and re-exposure events due to behavioral factors that favors infection in men.…”
Section: Sexual Dimorphism and Bacterial Infections In The Gastrointementioning
confidence: 99%
See 1 more Smart Citation